ED, email, emess!. Issue 1 (27th October 2011) - Hill, Daniel S; Cowling, Leigh; Jackson, Fleur; Parry, Richard; Taylor, Robert G; Wyatt, Jonathan P
Abstract : Email has transformed communication in the National Health Service. Handling a torrent of unfocused communication is a potential burden on the clinician's time and a source of stress at work. A prospective study of the number of emails, links and attachments received during a 14-day period by four doctors of an emergency department has revealed the large number of emails received, with consultants receiving more emails than registrars. The time required to merely read this mass communication is substantial. It is suggested that time needs to be allocated to handle emails and that doctors may benefit from training on how to handle them.